Vasoactive intestinal polypeptide level in gastroesophageal reflux disease before and after surgical treatment - Haidarzhi, Ye. I.; Holovko, M. H.; Okhrimenko, H. I.; Гайдаржі, Євген Іванович; Головко, Микола Григорович; Охріменко, Георгій Іванович (Запорізький державний медико-фармацевтичний університет, 2023)
The aim of the study was to examine the dynamics of plasma VIP during surgical treatment of GERD and its influence on the lower esophageal sphincter (LES) function. Materials and methods. Surgical treatment in the Nissen modification was performed for 35 patients with GERD. There were 26 women (74.3 %), men – 9 (25.7 %). mean age – 55.3 ± 11.3 years. Comparison group – 20 apparently healthy individuals: women – 14 (70.0 %); men – 6 (30.0 %), mean age – 56.7 ± 10.6 years. VIP was measured in venous blood plasma by an enzyme immunoassay (Vasoactive intestinal peptide ELISA, S-1201, BCM Diagnostics) using an immunoenzyme complex ImmunoChem-2100 (USA). The sampling of the studied samples in the main group was carried out before the operation and 2–3 months post-surgery. Results. In the main group before the surgery, the level of VIP was 3.1 ± 1.1 ng/ml, after the surgery – 2.2 ± 1.0 ng/ml. In the comparison group, VIP was determined at the level of 2.1 ± 1.1 ng/ml. In GERD before the surgery, the VIP level was statistically different from the indicators in the comparison group and from postoperative values. After surgical treatment, VIP values were decreased to the level of apparently healthy individuals. There was a positive correlation between the VIP level and acid exposure time (AET), the total number of refluxes, the number of reflux events longer than 5 minutes, the maximum duration of refluxes and the degree of esophageal inflammation. Мета роботи – вивчити динаміку ВІП у сироватці крові при хірургічному лікуванні ГЕРХ та його вплив на функцію нижнього стравохідного сфінктера (НПС). Матеріали та методи. Хірургічне лікування в модифікації Nissen здійснили 35 пацієнтам із ГЕРХ: 26 (74,3 %) жінок, 9 (25,7 %) чоловіків (середній вік – 55,3 ± 11,3 року). Група порівняння – 20 практично здорових осіб: 14 (70,0 %) жінок, 6 (30,0 %) чоловіків (середній вік – 56,7 ± 10,6 року). Дослідження ВІП здійснили шляхом імуноферментного аналізу в плазмі венозної крові. Зразки крові в пацієнтів основної групи брали перед операцією та через 2–3 місяці після неї. ВІП (Vasoactive intestinal peptide ELISA, S-1201, BCM Diagnostics) визначали на імуноферментному комплексі ImmunoChem-2100 (США). Результати. В основній групі до операції рівень ВІП становив 3,1 ± 1,1 нг/мл, після втручання – 2,2 ± 1,0 нг/мл. У групі порівняння ВІП визначили на рівні 2,1 ± 1,1 нг/мл. При ГЕРХ до операції рівень ВІП статистично відрізнявся від показника у групі порівняння та від післяопераційних значень. Після хірургічного лікування значення ВІП знизилися до рівня практично здорових пацієнтів. Виявили позитивний кореляційний зв’язок між рівнем ВІП і часом кислотної експозиції в стравоході, загальною кількістю рефлюксів, кількістю рефлюксів тривалістю понад 5 хвилин, максимальною тривалістю рефлюксів і ступенем запалення стравоходу.
Рівень вазоактивного інтестинального пептиду при гастроезофагеальній рефлюксній хворобі до та після хірургічного лікування
Haidarzhi Ye. I. - ORCID ID: 0000-0001-7211-1795; Holovko M. H. - ORCID ID: 0000-0003-1424-5554; Okhrimenko H. I. - ORCID ID: 0000-0003-0217-3549.
Keywords: gastroesophageal reflux disease; vasoactive intestinal peptide; гастроезофагеальна рефлюксна хвороба; вазоактивний інтестинальний пептид